FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA AKSEPTOR AKDR DI WILAYAH KERJA PUSKESMAS PURWOREJO - Wulandari, Fetty Chandra; Nisa, Zarra Fakhirotun (Jurnal Komunikasi Kesehatan, 2022)
Contraceptive methods used by family planning acceptors are dominated by short-term contraceptive methods, so that their effectiveness in controlling pregnancy is lower than other types of contraception (IUD). The purpose of the study was to determine the factors that influence the low number of IUD acceptors at PMB Rosida Himawati by using analytic survey methods and cross sectional design. The study population was all family planning acceptors at PMB Rosida Himawati. Sampling using accidental sampling technique with time in March-April 2022. Data analysis used univariate analysis and bivariate analysis. The results of the study based on the value of asyimp.sig = < 0.05 showed that there was no relationship between economic status and the lack of use of IUD contraceptives; there is a relationship between knowledge and lack of use of IUD contraception; there is a relationship between education and the lack of use of IUD contraception; and there is no relationshipbetween age and the lack of use of IUD contraception.